Corrosion and Mechanical Properties of the Fe-W-Wo₂ and Fe-Mo MoO₂ Nanocomposites - Yar-Mukhamedova, Gulmira; Ved, Maryna; Sakhnenko, Nikolay; Karakurkchi, Ann; Yermolenko, Iryna (My University, 2021)
Analyzing of composition electrolytic coatings’ application for the metal surface protection is considered. It is established that using different components for coatings’ modification gives possibility to obtain surfaces with expanding exploitation properties, in particular, with improved wearing and anticorrosion resistance. e new approach for protecting details which are made from cast irons by obtaining two kinds of composition coatings from binary alloys iron-molybdenum and iron-tungsten is proposed. It is found that the modification of iron by refractory metals up to 37 wt. % leads to a noticeable change in the microstructure of the coatings’ surface. It is established that the incorporation of refractory metals into the iron matrix is a good way to increase the microhardness of the surface by 2.5–3.5 times and rising of the wear resistance by 40%, as well as decreasing the friction coefficient by 3-4 times in comparison with the cast iron substrate. e research results can be used for surfaces hardening and protection in different industries.
Keywords: electrolytic coatings; microhardness; iron matrix; metals; nanocomposites